A Comparison of Malay Verbs with the Prefix of meN- and Their Equivalents in Chinese: (Perbandingan Kata Kerja Berimbuhan meN- Bahasa Melayu dan Padanannya dalam Bahasa Cina) (Jurnal Bahasa, 2020)
This paper reviews and compares the similarities and differences of meN- verbs and their equivalents in Chinese. The corpus of this study was selected from the entries and definitions in the bilingual dictionary Kamus Umum Bahasa Melayu-Cina Serba Baru, published in 2015. The main objective of this study is to investigate the differences and similarities of the two languages in order to shed some light on how the differences interfere in the acquisition of Malay by the users of this Malay-Chinese bilingual dictionary. This study employed the theory of interlingual contrast, Hartmann's theory of lexicography, and Nik Safiah's theory of Malay verbs and affixes. The interlingual contrast of meN- verbs and their equivalents indicate that meN- verbs in Malay and their equivalents in Chinese have both similarities and differences. The findings show that the most noticeable difference between the meN- verbs and their Chinese equivalents is that affixation and change of forms happen in Malay verbs but do not happen in Chinese verbs. Awareness of these differences is crucial for the compilation of Malay- Chinese bilingual dictionaries to help dictionary users, not only to comprehend but also to discern the meanings and uses of different meN-derived verbs.Keywords: meN- verbs, interlingual contrast, Malay-Chinese translation, bilingual dictionary